2021
DOI: 10.1155/2021/9795959
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Novel 60 GHz Millimeter Wave Q-Slot Antenna for Body-Centric Communications

Abstract: The 60 GHz band is a great prospect to meet the future demand for short-range indoor communication requiring wide bandwidth and high data rates. This paper presents the design of a 60 GHz printed Q-slot patch antenna for body-centric communication. The Q-slot has a slot gap of 0.2 mm and is etched on a 6.5 mm × 11 mm rectangular patch. The slotted patch is mounted on an FR-4 (Flame Retardant) substrate that is 1.6 mm thick and has a relative permittivity of 4.3. With a partial ground plane of length of 2.2 mm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The textile-based mmWave antenna presented by Wagih et al operating at 26 GHz and 28 GHz exhibited an on-body peak gain of 7 dB with 40% efficiency [25]. Aside from the research reviewed above, a few more studies on 5G and mmWave antennas for body area networks [25][26][27][28][29][30] have also shown promising results. A huge wideband array antenna operating at 60 GHz for body-centric communication has been 2…”
Section: Introductionmentioning
confidence: 99%
“…The textile-based mmWave antenna presented by Wagih et al operating at 26 GHz and 28 GHz exhibited an on-body peak gain of 7 dB with 40% efficiency [25]. Aside from the research reviewed above, a few more studies on 5G and mmWave antennas for body area networks [25][26][27][28][29][30] have also shown promising results. A huge wideband array antenna operating at 60 GHz for body-centric communication has been 2…”
Section: Introductionmentioning
confidence: 99%
“…The resonance frequency, polarization, radiation pattern, and impedance matching of a microstrip antenna can all fluctuate depending on the selected patch geometry [5]. While the literature overflows with various geometries accompanied by their respective design equations, including rectangular, circular, elliptical, square, triangular, polygonal, and nature-inspired shapes [6][7][8][9][10][11], some antenna configurations lack a comprehensive technical design methodology. Design equations for these configurations are either absent in the literature [12][13][14][15][16] or constrained due to variations in dielectric permittivity [17].…”
Section: Introductionmentioning
confidence: 99%
“…The results are compared with those of a conventional rectangular waveguide and other related studies in terms of gain, S11 and radiation pattern and shown advantages over them. In this paper, simulation results are only considered like that in [21] and [22]. Conducting measurements using a prototype of the fabricated antenna will be taken as a future work.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [21], proposed a design for the Q-slot antenna for the unlicensed 60 GHz band for body-centric communication. Computer Simulation Technology (CST) microwave studio was used to design and simulate the proposed antenna.…”
Section: Introductionmentioning
confidence: 99%